Effects of 12 Weeks of Continuous Exercise and Accumulation of Short-Duration Exercise on Body Composition, Physical Fitness, and Lifestyle Disease indices in Overweight Men in their 30s - Seong-Hoo Kim; Hyun-Seok Cho; Man-Gyoon Lee (Korea Institute of Sport Science, 2023)
PURPOSE This study aimed to investigate the effects of continuous exercise and the accumulation of short-duration exercise for 12 weeks on body composition, physical fitness, and lifestyle disease indices in overweight men in their 30s. METHODS Participants in the continuous exercise group (CE; n=13) performed a circuit exercise program of 30 min/session, 3 sessions/week for 12 weeks. Participants in the accumulation of short duration exercise group (ASE; n=12) performed the same exercise time of 30 min per day, divided into three sessions of 10 min. Body composition, physical fitness, and lifestyle disease indices were measured pre- and post-test and were compared by utilizing a repeated two-way ANOVA. RESULTS 1) Regarding body composition, body weight, body mass index, skeletal muscle mass, waist circumference, and fat mass decreased significantly, while hip circumference increased significantly in the CE group. Waist circumference and skeletal muscle mass decreased significantly, while hip circumference increased significantly in the ASE group. 2) Regarding physical fitness, right grip strength, sit and reach, sit up, and maximal oxygen uptake increased significantly in both groups. 3) Regarding hypertension indices, there were no significant differences in both groups, but they showed a tendency to improve. 4) Regarding hyperlipidemia indices, triglycerides (TG) decreased significantly in both groups, and total cholesterol (TC) decreased significantly in the CE group. 5) Regarding diabetes indices, there were no significant differences in both groups, but a tendency to improve was noticed. 6) Regarding arteriosclerosis indices: TG/high density lipoprotein-cholesterol ratio decreased significantly in both groups, and the TC/high density lipoprotein-cholesterol ratio decreased significantly in the CE group. CONCLUSIONS We concluded that both the accumulation of short duration exercise and continuous exercise can be effective in improving body composition, physical fitness, and lifestyle disease in overweight men.